EXPERIENCE OF APPLICATION OF VACUUM-ASSISTED CLOSURE IN NEONATES WITH SUPERFICIAL POSTSTERNOTOMY WOUND INFECTION AFTER CARDIAC SURGERY - A. A. Morozov; E. V. Grekhov; A. K. Latypov; N. A. Kotin; A. V. Vasilets; I. A. Kozyrev (Вестник хирургии имени И.И. Грекова)
OBJECTIVE. The study evaluated the efficacy of application of the method of vacuum-assisted closure in neonates with complicated healing of sternotomy soft tissue wounds after cardiac surgery. MATERIALS AND METHODS. Vacuum-assisted therapy of soft tissue of the thorax was performed on 9 patients with poststernotomy wound infection. The patients were infants aged 1 to 27 days (mean age 6 days) with weight from 2,3 to 3,6 kg (mean value 3,2 kg). RESULTS. The time of revealing the signs of incompetence of soft tissues of the thorax numbered 5-9 days. The duration of vacuum drainage was 5-14 days (mean value 9 days). Given period allowed clinicians to reach the effective wound cleansing and healing without problems after secondary closure. CONCLUSIONS. The application of the method was effective and healing of soft tissues of sternotomy wound of infectious and noninfectious nature was carried out in short terms in neonates after cardiac interventions.